The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4038/sljas.v13i0.2207
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal levels in two food fish species from Negombo estuary, Sri Lanka: Relationships with the body size

Abstract: The present study was carried out to assess the levels of eight metals viz. Pb, Cu, Cd, Ni, Cr, Mn, Hg and Zn in two species of food fish, Etroplus suratensis and Ambassis commersoni from Negombo estuary. The levels of Hg were analyzed by cold vapour atomic absorption spectrometry whereas the other metals were analyzed by flame/graphite furnace atomic absorption spectrometry. Total metal levels in muscle, gill and liver tissues of the fish showed a wide range. Accumulation of most metals in the tissues of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
4
22
2
Order By: Relevance
“…Flushing and the re-suspension of metals through the disturbance of sediment or soil would temporarily cause elevation of metal loads in water at a particular site (Eisenreich et al, 1980). Heavy metal levels observed in the present study for sediment in the Negombo lagoon are similar for Pb and Cr, whilst Cd values are higher than previously recorded values (Indrajith et al, 2008). It is also noteworthy that although Hg has been previously recorded in sediment from the Negombo lagoon (Indrajith et al, 2008), the present study did not detect this metal in any of the soil or sediment samples.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Flushing and the re-suspension of metals through the disturbance of sediment or soil would temporarily cause elevation of metal loads in water at a particular site (Eisenreich et al, 1980). Heavy metal levels observed in the present study for sediment in the Negombo lagoon are similar for Pb and Cr, whilst Cd values are higher than previously recorded values (Indrajith et al, 2008). It is also noteworthy that although Hg has been previously recorded in sediment from the Negombo lagoon (Indrajith et al, 2008), the present study did not detect this metal in any of the soil or sediment samples.…”
Section: Discussioncontrasting
confidence: 50%
“…The absence/low concentration of the heavy metals in the water reported here is in conflict with previously documented values for the Negombo lagoon. For instance, values reported by Indrajith & Pathiratne (2006) and Indrajith et al (2008) for Cd and Pb, and by Asanthi et al (2007) for arsenic, in water, were as high as 5.70, 2.10 and 2.16 µg/L, respectively. The seemingly contradictory results obtained in the present study could be viewed in the light of the conditions and processes that prevail in the lagoon.…”
Section: Discussionmentioning
confidence: 88%
“…Indrajith et al [23] reported lower values of cadmium and manganese in muscle and gills, lower values of cadmium and higher values in liver of Etroplus suratensis and Ambassis commersoni compared to the present study. Nwabueze [24] reported a higher mean accumulation for cadmium.…”
Section: Discussioncontrasting
confidence: 45%
“…Among the different metals analyzed, Pb and Cd are classified as toxic metals, which causes chemical hazards and therefore maximum residual levels have been prescribed for human consumption by various agencies of food standards [31-33]. Pb and Cd are biologically non essential metals which are acumulated in human tissues and harmful to human health [34]. …”
Section: Discussionmentioning
confidence: 99%